Educational policies in pandemic times - Galzerano, Luciana Sardenha (Argumentum, 2021)
Disputes over social policies during COVID-19 pandemic have been intense. In the educational ambit, social distancing measures resulted in the closure of schools and the subsequent need to adopt emergency policies to confront the educational challenges arising. This article aims to contribute to the analysis of these policies. One consequence is the risk of advancing the privatization of education. We consider that the State’s role in this process is central and that privatization must be understood in its complexity, not just as a redefinition of the border between public/state and private/non-state. For the analyses, we gathered information from official papers produced by Conselho Nacional de Educação and from documents released by national and international private organizations who influence the debates and decisions.